Publication trends of research on sepsis and programmed cell death during 2002–2022: A 20-year bibliometric analysis - Li, Jing-yan; Yao, Ren-qi; Xie, Min-yue; Zhou, Qi-yuan; Zhao, Peng-yue; Tian, Ying-ping; Yao, Yong-ming (Frontiers in Cellular and Infection Microbiology, 2022)
Background Sepsis is considered an intractable dysfunction that results from the disordered host immune response to uncontrolled infection. Even though the precise mechanism of sepsis remains unclear, scientific advances have highlighted the key role of various programmed cell death processes in the pathophysiology of sepsis. The current study aims to explore the worldwide research trend on programmed cell death in the setting of sepsis and assesses the achievements of publications from various countries, institutions, journals, and authors globally. Material and methods Associated publications during 2002–2022 with the topical subject of sepsis and programmed cell death were extracted from the Web of Science. VOSviewer was utilized to evaluate and map the published trend in the relevant fields. Results All 2,037 relevant manuscripts with a total citation of 71,575 times were screened out by the end of 1 January 2022. China accounted for the largest number of publications (45.07%) and was accompanied by corporate citations (11,037) and H-index (48), which ranked second globally. The United States has been ranked first place with the highest citations (30,775) and H-index (88), despite a low publication number (29.95%), which was subsequent to China. The journal Shock accounted for the largest number of publications in this area. R. S. Hotchkiss, affiliated with Washington University, was considered to have published the most papers in the relevant fields (57) and achieved the highest citation frequencies (9,523). The primary keywords on the topic of programmed cell death in sepsis remarkably focused on “inflammation” “immunosuppression”, and “oxidative stress”, which were recognized as the core mechanisms of sepsis, eventually attributing to programmed cell death. The involved research on programmed cell death induced by immune dysregulation of sepsis was undoubtedly the hotspot in the pertinent areas. Conclusions The United States has been academically outstanding in sepsis-related research. There appears to be an incompatible performance between publications and quantity with China. Frontier advances may be consulted in the journal Shock. The leading-edge research on the scope of programmed cell death in sepsis should preferably focus on immune dissonance-related studies in the future.